A de novo or germline mutation in a family with Mucolipidosis III gamma: Implications for molecular diagnosis and genetic counseling - Velho, Renata Voltolini (Mol Genet Metab Rep, 2014)
Mucolipidosis III (ML III) gamma is a very rare autosomal-recessive disorder characterized by the abnormal trafficking and subcellular localization of lysosomal enzymes due to mutations in the GNPTG gene. The present study consists of a report of a Brazilian compound heterozygote patient with ML III gamma resulting from one mutant paternal allele and one allele that had most likely undergone a de novo or maternal germline mutation. This is the first report of a de novo mutation in ML III gamma. This finding has significant implications for genetic counseling.